Case report: Long-term voluntary Tyrosine Kinase Inhibitor (TKI) discontinuation in chronic myeloid leukemia (CML): Molecular evidence of an immune surveillance - Imeri, Jusuf; Desterke, Christophe; Marcoux, Paul; Chaker, Diana; Oudrhiri, Noufissa; Fund, Xavier; Faivre, Jamila; Bennaceur-Griscelli, Annelise; Turhan, Ali G. (Frontiers in Oncology, 2023)
The classical natural history of chronic myeloid leukemia (CML) has been drastically modified by the introduction of tyrosine kinase inhibitor (TKI) therapies. TKI-discontinuation is currently possible in patients in deep molecular responses, using strict recommendations of molecular follow-up due to risk of molecular relapse, especially during the first 6 months. We report here the case of a patient who voluntarily interrupted her TKI therapy. She remained in deep molecular remission (MR4) for 18 months followed by detection of a molecular relapse at +20 months. Despite this relapse, she declined therapy until the occurrence of the hematological relapse (+ 4 years and 10 months). Retrospective sequential transcriptome experiments and a single cell transcriptome RNAseq analysis were performed. They revealed a molecular network focusing on several genes involved both activation and inhibition of NK-T cell activity. Interestingly, the single cell transcriptome analysis showed the presence of cells expressing NKG7, a gene involved in granule exocytosis and highly involved in anti-tumor immunity. Single cells expressing as Granzyme H, Cathepsin-W and Granulysin were also identified. The study of this case suggests that CML was controlled for a long period of time, potentially via an immune surveillance phenomenon. The role of NKG7 expression in the occurrence of treatment free remissions (TFR) should be evaluated in future studies.